Liming and phosphate fertilization for cassava in a dystrophic, very clayey, Dark-Red Latosol, "cerrado" phase - Nogueira, Francisco Dias; Paula, Miralda Bueno de; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment to evaluate the effects of liming and phosphate fertilization for cassava (Manihot esculenta Crantz) growth was carried out in a dystrophic, very clayey, Dark-Red Latosol, originally under cerrado vegetation, in the Experimental Farm Station of Felixlândia, MG, Brazil. After the chemical and physical characterization of the soil, the liming rates based upon the Al, Ca + Mg method were established at four levels: 0, 0.5, 1.0, 1.5 times the normal rate, equivalent to 0, 1950, 3900, 5850 kg/ha of dolomitic lime, having 80% of relative power of total neutralization. The phosphorus as triple superphosphate was applied at six P2O5 levels: 0 - 125 - 250 - 500 - 1000 - 2000 kg/ha. The maximum harvest estimated by regression analysis was 20,58 ton of roots/ha with 1448.6 kg of P2O5. The obtained data evidenced that under these conditions soil correction through liming and phosphate fertilization for cassava growth did not bring compensational benefits in terms of root and branches productivity. The greater Zn amounts in peciole and leaf were registered in the absence of liming and phosphate fertilization, suggesting that on soils under cerrado vegetation, where its availability is low, the occurrence of Zn deficiency symptoms can be induced by application of high corrective rates.